2021
DOI: 10.3390/ijerph182312477
|View full text |Cite
|
Sign up to set email alerts
|

Linking Emotional Intelligence, Physical Activity and Aggression among Undergraduates

Abstract: Several indicators are strongly related to health and well-being in university students, such as emotional intelligence and physical activity. At the same time, some qualities threaten it and are incompatible with students’ adaptation to society in general, such as aggressive behaviours. The aim of this research is to analyse the relationship established between emotional intelligence using TMMS-24, physical activity, using IPAQ, and aggression behaviours in university students. For this purpose, a descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…This is consistent with data from other studies that also reported direct associations between EI and exercise [ 3 , 29 , 30 , 31 , 32 , 33 ]. It is not surprising that people who exercise have better EI because they strive to be the best and often want to lead, and EI is an important trait for leadership [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with data from other studies that also reported direct associations between EI and exercise [ 3 , 29 , 30 , 31 , 32 , 33 ]. It is not surprising that people who exercise have better EI because they strive to be the best and often want to lead, and EI is an important trait for leadership [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Stanković et al concluded that elite athletes are characterized by positive, high scores in self-efficacy and emotionality [ 32 ]. Ubago-Jiménez found that the relationship between PA and EI is stronger in male than in female students [ 33 ]. Our finding of significant positive correlations between MVPA and EI for both men and women is consistent with earlier work.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to the General Aggression Model (GAM), aggression is associated with various social, cognitive, developmental, and biological factors [11]. However, previous studies have focused on the relationship between aggression and only one or two factors, including age [12,13], sex [10], chronic pain [14], low levels of physical activity [14,15], depression, anxiety [16][17][18][19][20], and marital status [21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these behaviors have a negative impact on both physical and mental health ( Reisig and Golladay, 2019 ; Choe et al, 2021 ). In this situation, emotions play a key role in the appearance and development of violent behaviors ( MacCann et al, 2020 ; Ubago-Jiménez et al, 2021 ) since they are a checkpoint for controlling one’s own impulses and the self-regulation of the person over himself ( Bacon et al, 2014 ; Beltrán-Catalán et al, 2018 ; Sorina et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%